Do novel oral anticoagulant drugs used in patients with nonvalvular atrial fibrillation act only as anticoagulants? - Cakmak, T.; Cakmak, E.; Balgetir, F.; Yasar, E.; Karakus, Y. (Verduci Publisher, 2023)
OBJECTIVE: Although inflamma-tion has an important role in the pathogenesis of atrial fibrillation (AF), the effect of novel oral an-ticoagulants (NOAC) used to reduce the risk of ischemic stroke and embolism on inflammation remains unknown. In this study, we aimed to in-vestigate the effects of NOAC, which have been shown to have anticoagulant properties, on in-flammation and platelet reactivation, which have an important role in the pathogenesis of AF.PATIENTS AND METHODS: A total of 530 pa-tients, including 380 patients with nonvalvular AF using NOAC and 150 patients with nonvalvu-lar AF who did not use any NOAC were included in the study. Neutrophil-to-lymphocyte ratio (NLR) was calculated as the ratio of absolute neutro-phil count to absolute lymphocyte count. Mean platelet volume (MPV), red cell distribution width (RDW), and neutrophil-to-lymphocyte ra-tio (NLR) values of both groups were assessed both on admission and at three-month follow-up. RESULTS: When the complete blood count (CBC) changes of the groups included in the study were compared, the RDW, MPV, and NLR values showed a greater decrease in the NOAC group compared to the non-NOAC group (p=0.000 for all).CONCLUSIONS: The results indicated that the NOAC used in anticoagulation treatment do not only act as anticoagulants but also re-duce inflammation and platelet reactivation, which have an important role in the pathogene-sis of AF and thromboembolism.
Keywords: Atrial fibrillation (AF); Novel oral anticoagulants (NOAC); Stroke; Inflammation; Mean platelet volume (MPV); Red cell dis-tribution width (RDW); Neutrophil-to-lymphocyte ratio (NLR)